Relationship between the Necessary Support Level for Oral Hygiene and Performance of Physical, Daily Activity, and Cognitive Functions - Yoh Tamaki; Yoshimune Hiratsuka; Toshiro Kumakawa; Hiroko Miura (Hindawi Limited, 2018)
To maintain good oral hygiene on their own, elderly adults need comprehensive abilities, such as physical, daily activity, and cognitive functions. In the long-term care certification, care support specialists conduct surveys that include a total of 74 items about physical function, daily activity function, living functions, cognitive function, mental/behavioral disorders, and adaption to social life. The data of the long-term care certification survey contain three items related to oral health: the necessary support level for oral hygiene, ability to swallow, and assistance with food intake. The aims of this study were to identify which functions are absent in elderly individuals who cannot maintain proper oral hygiene and to clarify at which stage it is necessary to assist elderly individuals with their oral hygiene and provide professional oral care. In this study, an analysis was conducted to identify the relationship between the necessary support level for oral hygiene and the performance of physical, daily activity, and cognitive functions. The results of the long-term care certification surveys were analyzed for 23,423 cases that involved 9,571 individuals who submitted a claim using long-term care statements between January 2009 and March 2018. The results of a multivariable logistic regression analysis showed that the following items had high odds ratios: "walk" and "stand up" in the physical and daily activity functions and the ability to "understand the everyday routine" and "make daily decisions" in the cognitive functions. The results of a decision tree analysis revealed that in order for elderly individuals to maintain good oral hygiene on their own, they must have adequate physical functioning as well as adequate performance of cognitive functions. Our study's findings suggest that comprehensive ability in both physical and cognitive functions is required for elderly adults to maintain their oral hygiene.